Cuerpo vivido e identidad narrativa en mujeres diagnosticadas con trastornos de la conducta alimentaria (2010)
ABSTRACT: Introduction: This paper shows the results obtained in the research about narrative identity and lived body in women diagnosed with eating disorders, which was conducted in Medellin during 2008. Objective: To recognize how the meaning given to the lived body reveals the construction of the identity of women with eating disorders. Methodology: Qualitative study with a multiple-case design that follows the procedures of the phenomenological hermeneutic method. This study complied with current ethical principles for research with human beings. For this purpose, each participant willingly signed the informed consent form. Techniques used were in-depth interview and focus groups. Results and Conclusions: Women diagnosed with anorexia-bulimia adopt the social model of beauty and attractiveness. They desire a competent body as a means of being successful, and therefore associate it with a thin body; the body and the “other” are the two main horizons in the identity construction of these women, the common thread is to live in order to accomplish a body and to show it. The possibilities of recovery do not simply involve the young woman eating and accepting her body, but rather prompting her to question the model of competent body by means of a narrative exercise that leads her to a new identity construction.